An Evaluation of the Viscoelastic Performance of Polystyrene Modified Asphaltic Binders. Issue 4 (November 2017) - Maharaj, Rean; Ramlochan, Demitri; Mohamed, Nazim
The addition of waste Polystyrene to Trinidad Lake Asphalt (TLA) and Trinidad Petroleum Bitumen (TPB) resulted in variations in the rheological properties of the modified blends as measured by changes in the phase angle, δ (measure of the elasticity) and the complex modulus, G * (measure of the degree of stiffness). Since TLA and TPB produced significantly different and in some cases contrasting results, this study offered supporting evidence confirming that the influence of the waste PS on the rheological properties of asphaltic binders cannot be generalized as it varies due to differences in source and chemical composition of the parent binder. The incremental addition of PS to TLA resulted in a significant increase in G * (up to 1.5 times for 10% added PS at 1.59Hz loading frequency) indicative of the incremental stiffening of the TLA. Stiffening was more pronounced at higher frequencies and was greater for the TLA modified blends compared those of TPB. The addition of 10% PS to TPB resulted in G * increasing by 79.4%, most of this increase occurring after the addition of only 1% PS (56.5%). The addition of 10% PS to the TLA base binder resulted in the δ value decreasing to 10.6 degrees from 38.1 degrees signifying a significant increase in elasticity. The influence of PS on TPB on the other hand resulted in a generally insignificant decrease in elasticity as s the addition of 10% PS resulted in δ increasing to 88.8 degrees from 87.7 degrees remaining an almost viscous liquid. This study demonstrates the ability to produce PS modified TLA and TPB blends of differing rheological characteristics offering the potential creation of customized asphalt-PS blends to suit special applications. This study highlights the potential of the blending of waste PS into asphalt as an environmentally attractive option for solving waste disposal issues.